Green regioselective synthesis and theoretical insights into photo- and thermochromic spiro heterocycles: toward optical and thermal sensing applications - Marzieh Jamali; Ali R. Sardarian; Farideh Rezaei; Afshan Mohajeri; Mohammad M. Ghanbari; Gyula Batta (Scientific Reports)
Abstract Building on the significant potential of pyrimidine-based molecules for optoelectronic applications, we designed and synthesized a new series of spiro[indoline-pyrido-pyrimidine] derivatives with excellent selectivity. These compounds exhibit novel photochromic and thermochromic properties, addressing the growing need for diagnostic agents with minimal side effects. The regioisomers were identified using 1D, 2D homonuclear and heteronuclear correlation NMR spectroscopy, along with X-ray crystallography. Dynamic 1 H NMR (DNMR) studies revealed that the major isomer (4 sa) is more stable than the minor isomer (4 sb). Optical, electrochemical, and structural analyses of compounds 4aa, 4ab, 4 sa, and 4sb demonstrated the feasibility of chemical reactions converting closed-ring structures to open-ring structures, resulting in notable optical properties due to ring opening. To validate the experimental data, density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were conducted at the B3LYP/6-31G(d) level, offering insights into the electronic structure and absorption spectra. Additionally, Gibbs free energy (ΔG) calculations were performed to elucidate the proposed mechanism for open-ring compounds named 5 and 7. This work emphasizes employing the citric acid as a bio-organic catalyst in a green, multi-component domino reaction, underscoring its environmentally sustainable approach. These studies reveal the potential of these compounds for advanced optical and temperature sensing applications, aligning theoretical and experimental approaches to establish a robust foundation for future research.